An Authentication for digital transaction with OTP using Color Code Systems (CCS) - Shivamurthaiah, M; Kumar Sinha, Sitesh; Praveen Kumar, K; Manasa, LR (International Journal of Computer Sciences and Engineering, 2025)
An Authentication for the digital transaction is a most vital problem. To secure any transactions through digital, mobile, internet, online system is very important. Nowadays India is gradually moving towards digital transactions. To make sure the confidential transactions are very important. The textual password for the Authentication is the most common method, here user need to memorize their passwords during their transaction, somewhere it is vulnerable to social engineering, cyber-attacks, and shoulder surfing. Regarding this, some graphical passwords are introduced to avoid the textual passwords. To address this problem, we can implement an application called color code system with OTP. It is a new technique based on the graphical password, in which here we use an OTP and color coding to solve the security problem. Here once the colors are exhibited with a specific rating, after this, some passwords are generated with some evaluation of colors, further the same colors are brought forth in a random path., we can insert the passwords according to the previous colors and ratings for user authentication which is called color code authentication, by this technique we can overcome the attacks like shoulder surfing.